Use of endoscopic naso-pancreatic drainage in the treatment of severe acute pancreatitis - Quan, Zhu-Fu (World J Gastroenterol, 2003)
AIM: To review the experience on the use of endoscopic nasopancreatic drainage (ENPD) in the treatment of severe acute pancreatitis (SAP). METHODS: Since March 1998, under the regular management of SAP with non-operative method, ENPD has been randomly used in 14 patients. The average age of the patients was 41.3 ± 15.9 (years), with 8 males and 6 females. The time from onset to admission was 32.9 ± 22.8 (hours). 8 cases were found to have gallbladder stone. The daily output of pancreatic fluid was measured. The body temperature, heart rate, WBC count, blood glucose, blood calcium, PaO(2), blood and urine levels of amylase were detected on the fifth day and compared with their respective data on the first day. Therapeutic results and hospitalization times were recorded. RESULTS: The time of drainage was 7.3 ± 4.0 days. The daily drainage outputs of the first five days were 236.4 ± 176.6, 287.1 ± 164.7, 284.6 ± 216.4, 435.0 ± 357.8 and 377.8 ± 223.8 ml, respectively. The decreases in body temperature, heart rate, WBC counts, blood and urine levels of amylase and the increase in PaO(2) were significant on the fifth day when compared with those on the first day. Infection of pancreatic necrosis was found in one patient and controlled by anti-infectives. 6 out of 8 patients with gallbladder stone were operated during hospital stay. All patients were cured and diischarged and the average hospital stay was 28.1 ± 11.6 days. CONCLUSION: ENPD is an effective method for the drainage of pancreatic fluid and might have an important role in the treatment of SAP. Further observation, comparison and summary by this method are worthy to be considered.